Induction of Subacute Ruminal Acidosis Affects the Ruminal Microbiome and Epithelium - McCann, Joshua C.; Luan, Shaoyu; Cardoso, Felipe C.; Derakhshani, Hooman; Khafipour, Ehsan; Loor, Juan J. (Frontiers in Microbiology, 2016)
Subacute ruminal acidosis (SARA) negatively impacts the dairy industry by decreasing dry matter intake, milk production, profitability, and increasing culling rate and death loss. Six ruminally cannulated, lactating Holstein cows were used in a replicated incomplete Latin square design to determine the effects of SARA induction on the ruminal microbiome and epithelium. Experimental periods were 10 days with days 1–3 for ad libitum intake of control diet, followed by 50% feed restriction on day 4, and ad libitum access on day 5 to the basal diet or the basal diet with an additional 10% of a 50:50 wheat/barley pellet. Based on subsequent ruminal pH, cows were grouped (SARA grouping; SG) as Non-SARA or SARA based on time <5.6 pH (0 and 3.4 h, respectively). Ruminal samples were collected on days 1 and 6 of each period prior to feeding and separated into liquid and solid fractions. Microbial DNA was extracted for bacterial analysis using 16S rRNA gene paired-end sequencing on the MiSeq Illumina platform and quantitative PCR (qPCR). Ruminal epithelium biopsies were taken on days 1 and 6 before feeding. Quantitative RT-PCR was used to determine gene expression in rumen epithelium. Bray–Curtis similarity indicated samples within the liquid fraction separated by day and coincided with an increased relative abundance of genera Prevotella, Ruminococcus, Streptococcus, and Lactobacillus on day 6 (P < 0.06). Although Firmicutes was the predominant phyla in the solid fraction, a SG × day interaction (P < 0.01) indicated a decrease on day 6 for SARA cows. In contrast, phylum Bacteroidetes increased on day 6 (P < 0.01) for SARA cows driven by greater genera Prevotella and YRC22 (P < 0.01). Streptococcus bovis and Succinivibrio dextrinosolvens populations tended to increase on day 6 but were not affected by SG. In ruminal epithelium, CLDN1 and CLDN4 expression increased on day 6 (P < 0.03) 24 h after SARA induction and a tendency for a SG × day interaction (P < 0.10) was observed for CLDN4. Overall, results indicate more rapid adaptation to an induced bout of SARA in the solid fraction ruminal microbiome compared with ruminal epithelium.